Au nom de la chair : manger, regarder et lire à cru - Krzykawski, Michał (Romanica Silesiana)
The aim of this paper is to elaborate on the fluid border that exists in French between la chair (flesh) and la viande (meat) as well as between la chair (flesh) and le corps (body). This blurry distinction spurs us to analyze the impact of the discovery of paintings in the Lascaux cave on our perception of art as connected to the realm of spirit. The uncanny character of the Lascaux cave paintings, a homage paid to animality, as well as an aspiration to the sacred, is identical with an irruption of the heterogeneous in the text. It turns art and literature into a space of excessive communication, which originates in flesh. Key words: Meat, flesh, body, steak, cannibalism, omophagy, blood, blood drinker, slaughterhouse, heterogeneity, cave.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />